Фаина Раневская : монолог - Щеглов Дмитрий Алексеевич (Герои без тайн, 2001)
Экземпляры: аб. (2001) / Инвентарный номер: 43369 / Цена: / Сис.шифр: 85.374(2) / Авт.знак: Щ 33 / ГРНТИ: 18.67 / ББК: 85.374(2)